Nontoxic, Inexpensive, Ammonium Chloride-Mediated (In Water) Synthesis of Some Novel 1,5-benzothiazepine Derivatives and Their Antimicrobial Activity - Coskun, Demet; Kirbag, Sevda (Chem Soc Pakistan, 2015)
In the present study, a new, nontoxic, easy and inexpensive method for the synthesis of 1,5-benzothiazepine derivatives was described and a mechanism for this reactions was proposed. Ammonium chloride which is inexpensive and readily available reagent catalyzes the thia-michael addition reaction of thiols in water efficiently. 1,5-benzothiazepines derivatives were synthesized by the condensation reactions of o-aminothiophenol (o-ATP) with chalcone derivatives by using saturated solution of NH4Cl in water. The products were characterized by the elemental analysis, NMR and FT-IR techniques. Synthesized compounds were tested for antimicrobial activity against. Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 25922, Bacillus subtilis IMG22 and Candida albicans ATCC 10231. Among the synthesized compounds 2b was found to be most active derivative against Escherichia coli ATCC 25922 and Candida albicans ATCC 10231. The other compounds didn't exhibit any activity against the other test microorganisms.
Keywords: Benzofuran; 1,5-Benzothiazephines; o-Aminothiophenol; Catalysis; Ammonium chloride; antimicrobial activity